SYNTHESIS HYDROTHERMAL ZINC STANNATE (ZN2SNO4) - Naupa R., A. R. (2010)
Zinc stannate (ZTO) was synthesised hydrothermally at 200 ºC for 16 h. The obtained material was characterized using X-ray diffraction (XRD) and transmission electron microscope (TEM). The main cristallite size was 40 nm calculated from its X-ray diffractogram. The photocatalytic activity of this material was tested by measuring the decomposition of an aqueous solution of methyl orange under UV light illumination. The result shows a degradation of 30% of the dye after 60 min of treatment.